THE "YEARBOOK OF THE INSTITUTE OF THE ROMANIAN REVOLUTION OF DECEMBER 1989"- A NEW ACADEMIC JOURNAL WITH INTERNATIONALLY RECOGNIZED SCIENTIFIC VALUE - Dan Vătăman (Romanian Journal of Historical Studies)
According to Law no. 556 of 7 December 2004, the Institute of the Romanian Revolution of December 1989 is the only public institution of national interest whose object of activity is the scientific analysis of the premises, development and effects - in political, economic and social terms - of the Romanian Revolution of December 1989, in order to achieve a documented, objective and comprehensive image of this cardinal event in the contemporary history of Romania.